Selective Abortion as Moral Failure? Revaluation of the Feminist Case for Reproductive Rights in a Disability Context - Claire McKinney (Disability Studies Quarterly, 2016)
Of feminism and disability theory's many overlapping concerns, few have received as much attention as prenatal genetic diagnosis and selective abortion. While the attention to how genetic selection reinforces disability stigma is important, much of this writing has failed to present the feminist case for the right to unrestricted abortion. This oversight has led to an articulation of the disability critique of selective abortion that threatens the very claims to reproductive freedom and bodily self-determination that undergird disability politics as well. This article rearticulates the feminist case for unrestricted reproductive rights in order to challenge the current framing of prenatal genetic diagnosis as an ethical failure and to present the opportunity to refigure reproductive rights as disability rights.